A comparative study of surface segregation and interface of La0·6Sr0·4Co0·2Fe0·8O3-δ electrode on GDC and YSZ electrolytes of solid oxide fuel cells. (6th January 2021) - Sun, Yi; He, Shuai; Saunders, Martin; Chen, Kongfa; Shao, Zongping; Jiang, San Ping
Abstract: Electrode/electrolyte interface plays a critical role in the performance and stability of solid oxide fuel cells (SOFCs). In the case of La0·6 Sr0·4 Co0·2 Fe0·8 O3-δ (LSCF) cathode, it is well known that cathodic polarization promotes the Sr segregation and diffusion towards the LSCF electrode and Y2 O3 –ZrO2 (YSZ) electrolyte interface, leading to the formation of SrZrO3 secondary phase and the disintegration of LSCF structure at the interface. On the other hand, LSCF is chemically stable with doped ceria electrolytes such as Gd-doped CeO2 (GDC). However, there appears no comparative studies on the intrinsic relationship between the surface segregation, interface reaction and stability of LSCF in YSZ and GDC electrolytes. Here, a comparative study has been carried out on the segregation and interface formation of LSCF on GDC and YSZ electrolyte under identical cathodic polarization conditions at 750 °C and 1000 mAcm −2 using focused ion beam and scanning transmission electron microscopy (FIB-STEM) techniques. Segregation of Sr occurs in the LSCF-GDC system, however, the inertness of GDC electrolyte suppresses the segregation process of Sr species. Instead, surface segregation of B-site Co cation becomes dominant under the cathodic polarization, forming isolated CoOx particles. The results indicate that the existence of chemical catchers such as Zr in the case of YSZ electrolyte for the segregated Sr species is kinetically the driving force for the Sr segregation and stability of LSCF electrodes under SOFC operation conditions. Highlights: LSCF/GDC and LSCF/YSZ electrodes were studied under identical conditions. Cathodic polarization induces the surface segregation of Sr in both electrodes. Sr segregation of LSCF/GDC is inhibited due to the inert of GDC electrolyte. Presence of catches such as Zr is the driving force for Sr segregation of LSCF/YSZ.